Analysis Factors of Diarrhea Incidentin Toddlers At Purwodadi District Health Centre, Grobogan. (Public Health Perspective Journal, 2019)
Diarrheal is an endemic disease in Indonesia and also becomedisease with extraordinary events which accompanied by death. There are many factors that can influence diarrhea, such as personal hygiene, environmental sanitation, children's nutritional status, and parental knowledge. The purpose of this study was to analyze the factors that influence the incidence of diarrhea in infants in Purwodadi I Health Center Grobogan. This research was a quantitative study, with a case control approach. The research sample was 92 samples with a purposive sampling technique. The instrument used questionnaires and observations. Data collection techniques of structured interviews used questionnaires, and observation sheets. Statistical analysis used Multiple Logistic Regression. The results found that the most influential variable among the other variables was maternal knowledge with p = 0,000. Whereas, the calculation of regression found that there is an influence on the age of mother p = 0.014, hand washing habit of mother p = 0.003, hand washing habit of toddler p = 0.019, and mother's knowledge p = 0,000 on the incidence of diarrhea in infants. The variables which are the main predictors in this study are the age of the mother, the skills of washing hands of mother, skills to wash the toddler's hands and mother's knowledge.